2016
DOI: 10.1371/journal.pone.0148437
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance of Commensal Staphylococcus aureus and Coagulase-Negative Staphylococci in an International Cohort of Surgeons: A Prospective Point-Prevalence Study

Abstract: Nasal colonization with antibiotic resistant bacteria represents both a risk factor for the colonized individual and their immediate contacts. Despite the fact that healthcare workers such as orthopedic surgeons are at a critical interface between the healthcare environment and an at-risk patient population, the prevalence of antibiotic resistant bacteria within the surgical profession remains unclear. This study offers a snapshot of the rate of nasal colonization of orthopedic surgeons with multi-resistant st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 67 publications
7
60
8
1
Order By: Relevance
“…We found that S. aureus strains of both the diabetes population and non-diabetes population in the present study were highly resistant to erythromycin and penicillin, which was similar to several other studies 20,38,39 . This might be as a result of the extensive use of these antibiotics in medical institutions.…”
Section: Discussionsupporting
confidence: 91%
“…We found that S. aureus strains of both the diabetes population and non-diabetes population in the present study were highly resistant to erythromycin and penicillin, which was similar to several other studies 20,38,39 . This might be as a result of the extensive use of these antibiotics in medical institutions.…”
Section: Discussionsupporting
confidence: 91%
“…The studies were published in 2008, (22) 2009, (14,15) 2010, (25) 2011, (23) 2012, (21) 2013, (12,13,16) 2014, (14,15,18) 2016, (20) 2017, (24) all in English. (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) In terms of level of evidence, 13 articles were cross-sectional, observational studies (level of evidence 6), (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) whereas one was a cohort study (level of evidence 4).…”
Section: Resultsmentioning
confidence: 99%
“…(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) In terms of level of evidence, 13 articles were cross-sectional, observational studies (level of evidence 6), (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) whereas one was a cohort study (level of evidence 4). (25) The studies were conducted in the following locations: USA, (12) Iran, (23,13) Brazil, (14,16,17,19,22) Ethiopia, (15) Sri Lanka, (18) Switzerland, (20) Libya,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations